Change-oriented OCB: Bagaimana peran psychological capital menunjang generasi Z ditempat kerja? - Fachry, Rey Anwar; Sofiah, Diah; Prasetyo, Yanto (JIWA: Jurnal Psikologi Indonesia, 2024)
Current cafes are usually filled with young employees, The young generation of this era is usually called generation Z is often known as the strawberry generation or the generation that is passionate and enthusiastic but cannot face social pressure and easily gives up when faced with problems. This research was conducted on generation Z who were working in cafes/coffeeshops in the Dukuh Pakis area and aged 18-28 years with a total of 127 out of 142 participants. This research used a quantitative method approach. Data collection was carried out using measurement instruments adapted to the Change-Oriented OCB scale (OCB-CH) and PCQ-24. Data analysis used the Spearman's Rho analysis technique with results showing a strong positive correlation between the two variables studied with a correlation coefficient of 0.469 with a significance level of 0.000 (p < 0.01). This means that the higher the level of Psychological Capital, the higher the level of OCB-CH behavior and otherwise, the lower the level of Psychological Capital, the lower the level of OCB-CH behavior. Keywords: Psychological Capital, OCB-CH, Cafe, Coffeeshop, Gen Z